Who's Going Green and Why? : Trends and Determinants of Green Investment - Eyraud, Luc (IMF Working Papers; Working Paper, 2011)
This paper fills a gap in the macroeconomic literature on renewable sources of energy. It offers a definition of green investment and analyzes the trends and determinants of this investment over the last decade for 35 advanced and emerging countries. We use a new multi-country historical dataset and find that green investment has become a key driver of the energy sector and that its rapid growth is now mostly driven by China. Our econometric results suggest that green investment is boosted by economic growth, a sound financial system conducive to low interest rates, and high fuel prices. We also find that some policy interventions, such as the introduction of carbon pricing schemes, or "feed-in-tariffs," which require use of "green" energy, have a positive and significant impact on green investment. Other interventions, such as biofuel support, do not appear to be associated with higher green investment.